Antibody response to SARS-CoV-2 mRNA vaccine among kidney transplant recipients: a prospective cohort study. (August 2021) - Rozen-Zvi, Benaya; Yahav, Dafna; Agur, Timna; Zingerman, Boris; Ben-Zvi, Haim; Atamna, Alaa; Tau, Noam; Mashraki, Tiki; Nesher, Eviatar; Rahamimov, Ruth
Abstract: Objectives: We aimed to evaluate the rates of antibody response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccine among kidney transplant recipients, and to identify factors associated with reduced immunogenicity. Methods: This was a prospective cohort study including consecutive kidney transplant recipients in a single referral transplant centre. Participants were tested for anti-spike (anti-S) antibodies 2–4 weeks after a second vaccine dose. Primary outcome was rate of seropositivity. Univariate and multivariate analyses were conducted to identify factors associated with seropositivity. Results: Of 308 kidney transplant recipients included, only 112 (36.4%) tested positive for anti-S antibodies 2–4 weeks after receiving the second dose of BNT162b2 vaccine. Median antibody titre was 15.5 AU/mL (interquartile range (IQR) 3.5–163.6). Factors associated with antibody response were higher estimated glomerular filtration rate (eGFR) (odds ratio (OR) 1.025 per mL/min/1.73 m 2, 95% confidence interval (CI) 1.014–1.037, p < 0.001), lower mycophenolic acid dose (OR 2.347 per 360 mg decrease, 95%CI 1.782–3.089, p < 0.001), younger age (OR 1.032 per year decrease, 95%CI 1.015–1.05, p < 0.001) and lower calcineurin inhibitor (CNI) blood level (OR 1.987, 95%CI 1.146–3.443, p 0.014). No serious adverse events resulting from the vaccine were reported. Conclusions: Kidney transplant recipients demonstrated an inadequate antibody response to SARS-CoV-2 mRNA vaccination. Immunosuppression level was a significant factor in this response. Strategies to improve immunogenicity should be examined in future studies.